2019
DOI: 10.1021/acs.jafc.8b04783
|View full text |Cite
|
Sign up to set email alerts
|

Toxic Effects and Possible Mechanisms of Deoxynivalenol Exposure on Sperm and Testicular Damage in BALB/c Mice

Abstract: Deoxynivalenol (DON, vomitoxin) is the most common mycotoxin in cereals and grains. DON contamination can cause a serious health threat to humans and farm animals. DON has been reported to exert significant toxicity effects on the male reproductive system. However, the causes and mechanisms underlying efforts of DON on sperm and testicular damage remain largely unclear. In the present study, we thoroughly investigated this issue. Eighty male BALB/c mice were randomly divided into a control group (n = 40) and D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 43 publications
(77 reference statements)
1
18
0
Order By: Relevance
“…Interestingly, the expressions of seminal caspases 3 and 9 observed in CS animals might be associated with the molecular apoptosis in the SVT. These results agree with previous reports about the presence of caspase 3 (do Nascimento et al, 2014;Jara et al, 2004;Tsounapi et al, 2017) and caspase 9 (Yang, Wang, et al, 2019;Yang, Zhang, et al, 2019) in male genital tracts under pathologic changes. Since TyrPho proteins essential for mature sperm physiology have been identified in testis, epididymis and seminal vesicle, many studies also demonstrated the changes of such proteins in CS testis Chaichun, Arun, Burawat, Kanla, & Iamsaard, 2017;Sawatpanich et al, 2018;Tongpan et al, 2019.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Interestingly, the expressions of seminal caspases 3 and 9 observed in CS animals might be associated with the molecular apoptosis in the SVT. These results agree with previous reports about the presence of caspase 3 (do Nascimento et al, 2014;Jara et al, 2004;Tsounapi et al, 2017) and caspase 9 (Yang, Wang, et al, 2019;Yang, Zhang, et al, 2019) in male genital tracts under pathologic changes. Since TyrPho proteins essential for mature sperm physiology have been identified in testis, epididymis and seminal vesicle, many studies also demonstrated the changes of such proteins in CS testis Chaichun, Arun, Burawat, Kanla, & Iamsaard, 2017;Sawatpanich et al, 2018;Tongpan et al, 2019.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, previous studies demonstrated overexpression of some SV proteins such as caspase 3 (do Nascimento, 2014;Jara, Carballada, & Esponda, 2004;Tsounapi et al, 2017) and caspase 9 (Yang, Wang, et al, 2019;Yang, Zhang, et al, 2019) in infertile animal models. Particularly, the changes of heat-shock protein 70 (Hsp70) are shown to associated with the reduction of SV components (Miyake, Muramaki, Kurahashi, Takenaka, & Fujisawa, 2008;Sahlén et al, 2010;Sundarraj, Raghunath, Panneerselvam, & Perumal, 2017;Tongpan et al, 2019).…”
mentioning
confidence: 91%
“…Another major impact of DOM‐1 was on sperm motility in vitro. It has been shown that chronic in vivo DON exposure reduced circulating testosterone concentrations and increased germ cell degeneration and induced abnormal sperm morphology in rats (Sprando et al, 2005) and reduced sperm motility in mice (Yang et al, 2019). Here we demonstrate a significant reduction in progressive motility of bovine sperm after 8 h exposure to DOM‐1 in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Busulfan-induced testicular injury mouse models are widely used as powerful tools for experiments involving spermatogonial stem cell transplantation, new treatments for nonobstructive azoospermia and preserving male fertility after chemotherapy, in which the noninvasive and dynamic evaluation of spermatogenic function is desirable (Ganguli et al, 2016;Sharma et al, 2019;Zhao et al, 2020). In The reduction in the number of germ cells in the busulfan-induced testicular injury model can lead to a decrease in the testicle-to-body weight ratio (Karna et al, 2019;Yang et al, 2019). Measurement of the testicle-to-body weight ratio is easy and enables comparison, but it can reflect only overall changes in the testes.…”
Section: Discussionmentioning
confidence: 99%
“…Busulfan-induced testicular injury mouse models are commonly used for experiments on spermatogonial stem cell transplantation, treatments for azoospermia due to spermatogenic failure and preserving male fertility after chemotherapy, in which evaluating spermatogenic function is essential (Ganguli et al, 2016;Sharma et al, 2019;Zhao et al, 2020). To evaluate spermatogenic function after busulfan treatment, several parameters, including the testicle-to-body weight ratio, percentage of tubules with spermatogenic cells and seminiferous tubule diameter, have been used (Karna et al, 2019;Udefa et al, 2020;Yang et al, 2019). However, all of these parameters have the same limitations.…”
Section: Introductionmentioning
confidence: 99%